Natural and Artificial Fiber-Reinforced Composites as Renewable Sources 2018
DOI: 10.5772/intechopen.70620
|View full text |Cite
|
Sign up to set email alerts
|

Waste and Recycled Textiles as Reinforcements of Building Materials

Abstract: Currently, the use of composite materials in the construction areas has had a great impact on the society; mainly, those related with sustainability and environment aspects. Daily proposals aimed at overcoming the properties of traditional materials that arise, which include emergent materials either from waste or recycled products. One of them is related to the textile materials, which include fibers such as wool, hemp, linen, and cotton. In the past decade, special attention has been focused on the used clot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…To produce 1 kg of cotton which approximately equals a pair of jeans and one T-shirt, more than 20,000 l of water and a lot of pesticides are used to ensure a good harvest. Denim jeans are among the most popular clothing textiles in the world consumer's demand and a significant part of global cotton production is be applied for denim fabric production [6]. The potential value of cotton textile waste as a source for textile reinforcements for the production of cost-effective and composites has been investigated [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…To produce 1 kg of cotton which approximately equals a pair of jeans and one T-shirt, more than 20,000 l of water and a lot of pesticides are used to ensure a good harvest. Denim jeans are among the most popular clothing textiles in the world consumer's demand and a significant part of global cotton production is be applied for denim fabric production [6]. The potential value of cotton textile waste as a source for textile reinforcements for the production of cost-effective and composites has been investigated [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Textile waste represents a source of raw materials for typical application in construction, such as insulation materials for noise and temperature and fillers or reinforcements of concrete [78]. The conversion of fibrous carpet waste into a value-added product as soil reinforcement demonstrated that fibrous inclusions derived from carpet wastes improve the shear strength of silty sands [79].…”
Section: Building/construction Materials From Textile Wastementioning
confidence: 99%
“…Fibers could also be those recovered from various waste streams, which could be suitable for lightweight concrete reinforcement (Zhou et al, 2010). Textile cutting waste has also been mixed with epoxy resin and foundry sand for producing a composite material used for lightweight construction (Pichardo et al, 2017). Regarding thermal insulation, thermal conductivity of the materials (λ) is the most important characteristic that should be considered since thermal conductivity is a measurement of the ability of a material to transmit heat.…”
Section: Textile As a Building Materialsmentioning
confidence: 99%
“…Moreover, fibrous materials have good sound absorbing potential. The acoustic efficiency of the textile was confirmed by analyzing the thermal and acoustic insulation, like cellulose fibers mixed into concrete (Paiva et al, 2011;Briga-Sa et al, 2013;Pichardo et al, 2017).…”
Section: Textile As a Building Materialsmentioning
confidence: 99%